Universities as legal entities and community dispute resolution: An Australian case study. Issue 12 (15th October 2019) - Martin, Jennifer
Abstract: This article considers the exercise of statutory power by an Australian university, in the state of Victoria, when undertaking commercial activities that impact negatively on a local community. A single case study design is used to report on the process engaged in by the community and university to resolve this dispute. This includes consideration of the university's characterisation of the activities it engaged in, the university bypassing local planning processes and the university's identification of the community with which to conduct its consultation processes. All publicly available documents regarding the proposed development were scrutinised as well as records of public forums related to the dispute. The study findings advance public understanding of the complexity of the vexed question of the extent to which university legislation can be used for commercial purposes and key issues for consideration when undertaking university–community engagement that have wider application for universities globally. John Dewey's philosophy of democracy and education provides valuable insights for developing democratic processes that facilitate deep understandings and good will that ultimately have the potential to enrich communities and prevent conflict.